2003
DOI: 10.1097/01.phm.0000087457.02231.fe
|View full text |Cite
|
Sign up to set email alerts
|

“Occult” Roentgenographic Osteoblastoma of the Cervical Spine

Abstract: A 33-yr-old man presented with a 4-yr history of neck pain. Previous work-ups, including planar radiographs and magnetic resonance imaging, were determined as "normal" by six previous consultants. In a subsequent in-office evaluation by a physiatrist, a vertebral osteoid osteoma or carotid artery angiitis was clinically suspected. A bone scan of the cervical spine was consistent with a the presence of an of osteoid osteoma. Thereafter, repeat magnetic resonance imaging confused the issue by suggesting the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…Plain radiography is the most common radiological choice and is thought to have great value for diagnosing spinal OBLs [17][18][19][20]. However in our study, normal images were found in half of the patients with CO and onefourth of cases with AO, which might cause a high number of misdiagnoses if it were the only diagnostic tool used.…”
Section: Discussioncontrasting
confidence: 59%
“…Plain radiography is the most common radiological choice and is thought to have great value for diagnosing spinal OBLs [17][18][19][20]. However in our study, normal images were found in half of the patients with CO and onefourth of cases with AO, which might cause a high number of misdiagnoses if it were the only diagnostic tool used.…”
Section: Discussioncontrasting
confidence: 59%
“…The typical plain radiographic feature of the lesion is a lytic and expansile lesion [1,7,8,17,20], as in our case (fig. 1).…”
Section: Discussionmentioning
confidence: 59%
“…This lesion occurs 4 times less often than osteoid osteoma and is 20 times less frequent than osteosarcoma [1,3,4,8,9,17,20]. Benign osteoblastoma was independently described in 1956 by both Jaffe [14] and Lichtenstein [21].…”
Section: Discussionmentioning
confidence: 99%
“…On MRI, they commonly exhibit edema of the surrounding marrow and soft tissues. 43,47,48 Osteosarcoma Osteosarcoma is the most common nonhematological primary malignancy of bone and has been extensively documented in the appendicular skeleton. The mean age of inci- dence in the fourth decade, which is two decades later than the mean age of its appendicular counterpart.…”
Section: Osteoblastomamentioning
confidence: 99%